Efektivitas Senam Nyeri Haid (Dysmenorrhea Gymnastics) terhadap Penurunan Intensitas Nyeri pada Remaja Putri - Rina Kurnia Dewi; Yuni Purwati; Sri Riyana (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Primary dysmenorrhea is a widespread condition affecting many adolescent girls, taking a serious toll on both their general well-being and their success in the classroom. Non-pharmacological interventions, such as dysmenorrhea exercises, are essential as safe alternatives to mitigate reliance on long-term analgesic use. The primary objective of this study was to evaluate whether dysmenorrhea exercises could effectively mitigate menstrual pain intensity in adolescent girls at SMPN 2 Sleman, Yogyakarta. The research was conducted using a quantitative pre-experimental approach with a one-group pretest-posttest design. The participants consisted of 18 female students selected via purposive sampling based on specific inclusion criteria (aged 12–14 years, experiencing menstrual pain, and having regular menstrual cycles). The exercise intervention was administered over two days, with a duration of 15–30 minutes per session. Pain intensity was measured using the Numeric Rating Scale (NRS). Data was analyzed using the Wilcoxon Signed-Rank Test with a significance level of α < 0.05. The results indicated a significant decrease in the mean pain score from 5.78 (pre-test) to 2.56 (post-test). The statistical test yielded a p-value of 0.000. A clinically meaningful change was observed, where the majority of respondents (88.9%) reported mild pain after the intervention, compared to the pre-intervention condition dominated by moderate pain (77.8%). These findings demonstrate that dysmenorrhea exercises are significantly effective in reducing dysmenorrhea pain intensity among adolescent girls. Consequently, this intervention is recommended as a non-pharmacological pain management strategy in school settings.